Simulation of the flow pattern around spur dykes using FLUENTS - Othman A. Karimb,; K.H.M. Ali, (1999)
The ultimate objective of this study is the prediction of flow pattern associated with spur dykes. Prediction of velocity fields and bed shear stresses were obtained using the FLUENT package. The RNG k-eformulation in FLUENT has been validated against selected benchmark solutions of flow in the vicinity of spur dykes. Extensive testing procedures have been implemented to ensure that the equations and solution algorithms used by FLUENT would provide an accurate simulation of flow. Experiments carried out by Mayerle et al. (1995) and Zaghloul and McCorquodale (1975) were selected as benchmark for verification purposes. FLUENT predicted reasonably Iwell the attachment point downstream of the dyke in the flat-bed case. Calculated bed shear stresses can then be used in appropriate sediment continuity equations for the prediction of scour hole geometries